BVGer D-959/2023 vom 13. Januar 2023 - Bundesverwaltungsgericht (2023)
Asyl und Wegweisung (Mehrfachgesuch/Wiedererwägung) | Asyl und Wegweisung (Mehrfachgesuch/Wiedererwägung); Verfügung des SEM vom 13. Januar 2023